ELT in Indonesian Context: Which One is Better? NESTs or NNESTs - Ahmad Madkur (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2017)
Teachers are unquestionably a vital factor in the field of education and English teaching is no exception. Good teachers of English language must acquire, at minimum, three main skills: linguistic, pedagogic and cultural skills. In Indonesia, nowadays, many schools and universities not only employ non-native English speaking teachers (NNESTs) who are of course Indonesian, but also native English speaking teachers (NESTs). This condition draws pros and cons and therefore it is important to know more deeply about the two kinds of teachers. This paper attempts to discuss the strength and weaknesses of both teachers. This discussion concludes that for ELT in Indonesian context, NNESTs should be prioritized more than NESTs. Keywords: teachers, ELT, NNESTs, NESTs